AB0698 Overlaping Spondylarthritis and Periodic Autoinflammatory Syndrome? A "Bed to Bench" Story. (10th June 2014) - von Mühlenen, I.; Finckh, A.; Roux-Lombard, P.; Gabay, C.
Abstract : Background: The diagnosis of Spondylarthritis remains a challenge (1). We present a case series of patients with overlaping clinical manifestations of Spondylarthritis and autoinflammatory Syndromes making the diagnosis difficult. Objectives: We hypothesized that SpA and other autoinflammatory syndromes may coexist. Methods: We provide a brief clinical description of several patients initially diagnosed only as SpA. We performed a genetic analysis of these patients and of their family members, focusing on well-characterized hereditary autoinflammatory syndromes. Results: Patient (P1) presented with undifferentiated arthritis and exhibited some clinical and radiological characteristics of Spondyloarthritis (SpA), including inflammatory back pain, inflammatory arthralgias, sacro-iliitis on MRI, high acute-phase response (CRP and ESR), but negative HLA B-27. The disease activity and acute-phase response remained high despite anti-TNF and c-DMARD therapy. Because the patient also complained of abdominal pain, myalgia and urticaria, we searched for an immunodeficiency and found high levels of IgD. Two other patients (P2 and P3) were consequently identified with similar clinical and laboratory features, including inflammatory back pain and arthralgias, high acute-phase response, negative HLA B-27, high serum IgD levels and only limited responsiveness to c-DMARDs and TNF-inhibitors. P1 was found to have a heterozygous mutation in the MEFV- Gene (K695R) suggestive of FMF. P2 carries a heterozygous mutation in the TNFRSF1A gene (R92Q) and a heterozygous mutation in the MEFV-gene (E148Q), suggestive of FMF and TRAPS. No mutations were found for P3. In family of P1 (SpA & FMF), the same mutation was found in the mother, the sister and 3 nieces. Of note, the sister also has SpA and one of the nieces, also displays high IgD, arthralgias, abdominal pains and severe aphthosis. In family of P2 (SpA-FMF-TRAPS), both mutations were found in his/her mother and two sisters. His/her father displayed typical features of SpA, the mother had episodes of pleuritis and abdominal pain and the two sisters had similar, though less severe, clinical manifestations as the index patient. Conclusions: Our findings support the presence of overlapping clinical manifestations between SpA and periodic fever syndromes in some patients. These patient's low penetration genetic mutations may have influenced the clinical manifestations of SpA. SpA in general does have some autoimmune but also some autoinflammatory features (2). High serum levels of IgD are commonly reported in some autoinflammatory diseases and may represent a useful biomarker for these overlap presentations between SpA and autoinflammatory diseases. References: Are Spondylarthritides related but distinct conditions or a single disease with heterogeneous phenotype? Dominique Baeten, Maxime Breban, Rik Lories, Georg Schett and Joachin Sieper. Arthritis and Rheumatism Vol. 65, No 1, January 2013, pp 12-20 Pathogenesis of Spondyloarthritis: autoimmune or autoinflammatory? C. Ambarus et al. Curr Opin Rheumatol 2012, 24:000-000 Diagnostic value of serum immunoglobulinaemia D level in patients with a clinical suspicion of hyper IgD syndrome. W. Ammouri et al. Rheumatology 2007;46: 1597-1600. Disclosure of Interest: I. von Mühlenen Grant/research support: Novartis, A. Finckh Grant/research support: Novartis, P. Roux-Lombard Grant/research support: Novartis, C. Gabay Grant/research support: Novartis DOI: 10.1136/annrheumdis-2014-eular.3669